Ultrasound-guided injection technique of the equine cervical nerve roots - Fouquet, Gregoire; Abbas, Ghazanfar; Johnson, Jessica P.; Pompermayer, Endrigo; Harel, Camille; Aldous, Eman; Puchalski, Sarah; David, Florent (Frontiers in Veterinary Science, 2022)
Radiculopathy in horses is often a diagnosis of exclusion because of the non-specific clinical signs related to neck pain and possible forelimb lameness. There are no reported treatment options in the equine veterinary literature. The purpose of the study was to describe an ultrasound-guided injection of the cervical nerve root C3 to C8, to evaluate accuracy, time and safety and to anticipate possible complications on clinical cases. Under general anesthesia and with ultrasound guidance, five horses were injected from C3 to C8 with 1.5mL mix of contrast and latex. Immediately after euthanasia, the necks were taken for CT examination and then dissection was performed 3 days later. Data regarding the accuracy of injection, the presence of injectate in the nerve root, vertebral vessel or vertebral canal were recorded from both CT and dissection. The time of injection and ability to visualize the nerve root prior to injection were also recorded. Out of 60 intended injections, 55 (CT images) and 57 (dissection) led to injectate deposited within the target zone with direct contact between contrast/latex and cervical nerve roots noted in 76.4% and 73.7%, respectively. Presence of contrast/latex injectate within nerves (≤11%), vertebral vessels (<4%) and canal (<4%) were rarely encountered. No variation on success rate or safety noted based on the site of injection. The technique described has excellent accuracy, with injectate deposition in direct contact (75%) or close vicinity (25%) of C3-C8 cervical nerve roots. Injectate diffusion is likely to further improve success rate. Rare presence of injectate within nerve/sheath, vertebral vessels/canal along with diffusion warrants caution when performing this procedure in clinical cases.